2020
DOI: 10.1101/2020.08.16.252858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assembly of the algal CO2-fixing organelle, the pyrenoid, is guided by a Rubisco-binding motif

Abstract: Approximately one-third of the Earth’s photosynthetic CO2 assimilation occurs in a pyrenoid, an organelle containing the CO2-fixing enzyme Rubisco. How constituent proteins are recruited to the pyrenoid, and how the organelle’s sub-compartments - membrane tubules, a surrounding phase-separated Rubisco matrix, and a peripheral starch sheath - are held together is unknown. Using the model alga Chlamydomonas reinhardtii, we discovered that pyrenoid proteins share a sequence motif. We show that the motif is suffic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…An emerging theme of CCM self-assembly is that Rubisco interacts with various CCM proteins via Short Linear Motifs (SLiMs) found in intrinsically disordered proteins/regions (IDP/Rs) (27)(28)(29). Since CsoSCA's N48-peptide appears to bind Rubisco (Fig.…”
Section: Structure Of Rubisco In Complex With Csosca Ntd Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…An emerging theme of CCM self-assembly is that Rubisco interacts with various CCM proteins via Short Linear Motifs (SLiMs) found in intrinsically disordered proteins/regions (IDP/Rs) (27)(28)(29). Since CsoSCA's N48-peptide appears to bind Rubisco (Fig.…”
Section: Structure Of Rubisco In Complex With Csosca Ntd Peptidementioning
confidence: 99%
“…In contrast to these bacterial systems, in the model algae Chlamydomonas reinhardtii a repeat SLiM in the disordered scaffolding protein EPYC is essential for pyrenoid formation (42,43) and binds on top of the small subunit via salt bridges and a hydrophobic interface (28). The sequence motif is shared among many pyrenoid proteins, suggesting a mechanism for protein targeting as well as more broadly organizing pyrenoid ultrastructure (29). The versatility in binding motif and binding site, and the convergent function of diverse Rubisco as a hub of interaction implies this might be a general feature, which raises a final question.…”
Section: Rubisco As An Interaction Hub In Biophysical Ccm'smentioning
confidence: 99%
“…Then, the newly formed matrix needs to be positioned proximal to low-pH thylakoids, and the thylakoid CA needs to be localized to the pyrenoid-proximal thylakoid lumen. Recent work in Chlamydomonas has shown that a Rubisco-binding motif targets proteins to the pyrenoid, and appears to link the matrix to the intra-pyrenoid tubules and starch sheath (70), thus providing a framework for manipulating the organization of an engineered pyrenoid. For example, constructing a fusion protein of the plant thylakoid CA and a membrane protein containing the Rubisco-binding motif may promote the desired colocalization of the pyrenoid matrix, thylakoids, and thylakoid CA.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrenoidsthe microalgal subcompartments in which RuBisCO is often located to facilitate higher local CO 2 concentrationsare another complication facing the expression of heterologous RuBisCO in microalgae. It was recently determined that the pyrenoid compartment assembles by specific binding of pyrenoid-associated proteins to RuBisCO [43]. This assembly is likely disrupted when replacing a native RuBisCO by a heterologous candidate.…”
Section: Improving Carbon Fixationmentioning
confidence: 99%